Audiovisual Translation as A Didactic Tool to Enhance Foreign Language Speaking Skills: Introduction - Sánchez Requena, Alicia; Frumuselu, Anca Daniela (Journal of Audiovisual Translation, 2024)
This current thematic section explores the growing field of didactic audiovisual translation (DAT) and its impact on foreign language (FL) learning, particularly in enhancing FL speaking skills. In the last twenty years, several European-funded projects and independent researchers, have delved into the use of audiovisual translation modes such as subtitling, voice-over, dubbing, and audio description in FL education. The present thematic section gathers six studies that focus on the use of DAT to improve speaking skills, an area often underexplored. The contributions of various scholars examine the effectiveness of different DAT modalities (dubbing, audio description, free commentary, voice-over and respeaking) in enhancing speaking skills, including pronunciation, intonation, and pragmatic training, in a variety of FL such as English, Spanish, and Italian.